2022
DOI: 10.1111/bjet.13185
|View full text |Cite
|
Sign up to set email alerts
|

Online aviation learning experience during the COVID‐19 pandemic in Hong Kong and Mainland China

Abstract: The COVID-19 pandemic has triggered an unexpected digital revolution, speeding up universities' digital transformation worldwide. It has brought heavy disruptions to travel and mobility worldwide, but it drives the opportunity for hosting region-wide or even international academic exchanges through learning programs, workshops, and conferences via an al-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 108 publications
(133 reference statements)
1
30
0
3
Order By: Relevance
“…Kearns (2016) found that the quality of virtual aviation courses is way too diversified: some courses directly transformed conventional classroom delivery to online mode without thoroughly considering the difference between the two environments. Also, Ng (2022) concluded that students criticise online teaching pedagogy based on its effectiveness. While virtual teaching might lack the components for essential practices, students find the lesson recordings from this teaching mode useful as they can review them any time after the lesson.…”
Section: Policy and Managerial Insightsmentioning
confidence: 99%
“…Kearns (2016) found that the quality of virtual aviation courses is way too diversified: some courses directly transformed conventional classroom delivery to online mode without thoroughly considering the difference between the two environments. Also, Ng (2022) concluded that students criticise online teaching pedagogy based on its effectiveness. While virtual teaching might lack the components for essential practices, students find the lesson recordings from this teaching mode useful as they can review them any time after the lesson.…”
Section: Policy and Managerial Insightsmentioning
confidence: 99%
“…A study conducted by Mystakidis et al (2021) suggested the use of a CoI, where students could build their personal connections to establish collaboration, communication and social presence, thus offering deep and meaningful learning experiences for students in social VR environments. I have highlighted the importance of social and cognitive support to discuss how to foster students' engagement in an aviation virtual laboratory setting with the use of flight simulation and virtual tours (Ng, 2022a(Ng, , 2022b. Similarly, Williams et al (2022) integrated meaningful learning in VR organic chemistry laboratories to provide immersive and realistic experiences for students, and reduce students' attendance challenges and safety concerns.…”
Section: Metaverse As a Community Of Inquiry (Coi)mentioning
confidence: 99%
“…These papers explore the coping mechanisms among the Eastern and Western universities for emergency remote teaching (ERT) during the pandemic, the impact of ERT on students and staff, and also some of the implications for post-pandemic improvement. Ng (2022) analyses the effectiveness of a month-long online aviation programme implemented in Mainland China and Hong Kong universities for undergraduate aviation and tourism students. He argues that even though students were motivated to learn online, and appreciated the collaborative and 'hands-on' opportunities offered by online learning, they prefer blended learning, since face to face teaching enables them to have a proper contact and social interactions with their peers, and also industry professionals in a physical environment.…”
Section: Overvie W Of the Speci Al Sectionmentioning
confidence: 99%